Histological Description of Meningeal and Periosteal Dural Layers at the Porus of Internal Acoustic Canal in the Vestibular Schwannoma - Sutiono, Agung Budi; Arifin, Muhammad Zafrullah; Faried, Ahmad; Ohira, Takayuki (International Journal of Integrated Health Sciences, 2013)
Objective: To study the transformation point of meningeal and periosteal dural at the porus of internal acoustic canal (IAC) in order to verify the different thickness of meningeal and periosteal dura in vestibular schwannomas (VS). Methods: Three IAC cadaver specimens and ten samples of VS patients from porus were obtained and analyzed. Samples were stained by using Masson trichrome technique after cutting in 6 micron of thickness. The samples were then observed under light microscopes to understand the meninges pattern in the IAC. Results: The meningeal dura is becoming thin at the porus and disappears at the meatal portion to form epineurium. However, the periosteal dura is lining continuously to the fundus. In VS, the meningeal dura becomes thick and forms a pseudo-capsule in the middle of meatus, known as perineurium. The residual nerve filament was compressed by the tumor parenchyma. Between the tumor and nerve interface, three or more perineureal layers are seen. The perineurium in the cisternal portion was consistently loose and forms the tumor and arachnoid nerve interface. Almost all the nerve filaments are displaced to the tumor periphery near the pseudocapsule. In contrast, the periosteal dural of VS is becoming thin and disappear nearby the middle of meatal portion. This changing site establishes “meningo-periosteal ring” of VS because of the encircling nearby the porus. Conclusions: In IAC, the meningeal dural becomes thin. The periosteal dura is lining continuously to the fundus. In VS, the meningeal dura becomes thick, joins perineurium and forms pesudocapsule near the porus, but the periosteal dura disappeared. This changing point is called meningo-periosteal ring.     Keywords: Meningeal,  periosteal, porus, vestibular schwannomasDOI: 10.15850/ijihs.v1n1.104